The Solution To The Ambivalence Of The Presence Of Foreigners To The Indonesian Public Welfare: Inevitability Of Immigration Toward WBK/WBBM - Muchlas Abdi Pratama; Amalia Wiliani; Anita Diana Sari (Jurnal Ilmiah Kajian Keimigrasian, 2020)
In the era of globalization, the intensity of human traveling between countries is getting higher. It influences the foreigners in Indonesia becoming greater in number every year. This condition creates ambivalent impacts on public welfare. On the one hand, the influx of foreigners spending their money on tourism, not to mention their funds in investment, can help empower the society in Indonesia. On the other hand, it can be a threat to the society if many foreigners commit wrongful deeds like breaking the rules for becoming illegal workers. For their presence in Indonesia, foreigners could contribute to the public welfare, so a bureaucratic reform is needed since a bad bureaucratic caused many foreigners to commit wrongful deeds or even be hesitant about visiting Indonesia. One of the ways to reform the bureaucracy is by building Integrity Zone for Corruption-free Zones (WBK) and the Serving and Clean Bureaucracy Zone (WBBM), especially in the area of Directorate General of Immigration.